Cavity nesting waterfowl in Minnesota - Zicus, Michael C; Hennes, Steven K (Wildfowl, 1988)
Cavity nesting waterfowl pose difficult census and survey problems. A total of 13,219 waterfowl nest box checks from 1979 to 1985 were used to document further the current breeding distribution of cavity nesting waterfowl in Minnesota and to estimate their relative abundance in relation to 18 landscape regions. Wood Duck nesting was documented in 10 additional counties and was most common in the Deciduous Forest Formation. In comparison, Hooded Mergansers, Common Goldeneyes, and Common Mergansers were most common in the Coniferous Forest Formation. These 3 species were documented as nesting in 9, 4, and 1 counties respectively, not listed by Janssen and Simonson (1984). Continued efforts to improve measures of the distribution and relative abundance of cavity nesting waterfowl in relation to land-use patterns will further our understanding of their ecology and improve their management.